2012
DOI: 10.1002/jmv.23438
|View full text |Cite
|
Sign up to set email alerts
|

Human metapneumovirus associated with community‐acquired pneumonia in children in Beijing, China

Abstract: Community-acquired pneumonia is a major cause of morbidity and mortality in children worldwide. However, few studies have been conducted on the infection of human metapneumovirus (hMPV) associated with pediatric community-acquired pneumonia in China. Nasopharyngeal aspirates were collected between July 2008 and June 2010 from 1,028 children, aged ≤16.5 years, who were diagnosed with community-acquired pneumonia in Beijing, China. Reverse-transcriptase polymerase chain reaction was used to screen the samples fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
13
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 38 publications
10
13
0
Order By: Relevance
“…Previous studies have reported the prevalence of certain predominant hMPV genotypes in a given year. hMPV sub-genotypes may vary in different years and alternative predominance of hMPV sub-genotypes has been observed [Matsuzaki et al, 2008;Pitoiset et al, 2010;Kim et al, 2012;Lu et al, 2013;Wei et al, 2013]. The present study found that the epidemiological characteristics and clinical features were fundamentally similar among patients infected with different genotypes of hMPV, which is consistent with the results of some studies [Bosis et al, 2008;Wei et al, 2013].…”
Section: Discussionsupporting
confidence: 91%
“…Previous studies have reported the prevalence of certain predominant hMPV genotypes in a given year. hMPV sub-genotypes may vary in different years and alternative predominance of hMPV sub-genotypes has been observed [Matsuzaki et al, 2008;Pitoiset et al, 2010;Kim et al, 2012;Lu et al, 2013;Wei et al, 2013]. The present study found that the epidemiological characteristics and clinical features were fundamentally similar among patients infected with different genotypes of hMPV, which is consistent with the results of some studies [Bosis et al, 2008;Wei et al, 2013].…”
Section: Discussionsupporting
confidence: 91%
“…Besides a close phylogenetic relationship of hMPV and RSV [7,8], clinical symptoms are very similar and rated as indistinguishable [6,9]. Just like RSV, hMPV can cause uncomplicated infections of the upper airway up to severe bronchiolitis and community-acquired viral pneumonia [10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…According to preexisting studies, hMPV can be detected as pathogen in 5-14% of pediatric patients with symptoms of an acute respiratory infection [11,12,14].…”
Section: Introductionmentioning
confidence: 99%
“…5 Since then, hMPV has been detected in 4-16% of patients with ARIs. [6][7][8] The incidence of hMPV may vary from year to year in the same area. 9 hMPV causes disease primarily in children, but can infect adults and immunocompromised individuals as well.…”
Section: Introductionmentioning
confidence: 99%